PELATIHAN PENINGKATAN KAPASITAS PETANI MILENIAL - Reny Sukmawani; Endang Tri Astutiningsih; Amalia Nur Milla; Neneng Kartika Rini; Sistiana Windyariani; Andri Moewashi IH (Department of Agricultural Product Technology, Faculty of Agricultural Technology, Universitas Andalas Kampus Limau Manis - Padang, Sumatera Barat Indonesia-25163, 2023)
Pelatihan peningkatan kapasitas petani milenial dilaksanakan dalam bentuk Pendidikan dan latihan (diklat) yang terangkum dalam kegiatan diklat capacity building bagi petani milenial. Tujuannya adalah untuk (1) menyiapkan petani milenial yang mampu menjadi agen perubahan yang berdaya dan mampu memberdayakan potensi sumberdaya yang ada dimasyarakat; (2) meningkatkan kapasitas petani milenial secara individu dan organisasi dalam mencapai tujuan dan (3) terciptanya kelompok petani milenial yang sehat, tangguh dan mandiri. Diklat CB dilaksanakan melalui bimbingan teknis pada 7 (tujuh) kegiatan bimbingan melalui pendekatan partisipatif. Hasil kegiatan menunjukan bahwa indikator kesatu dan kedua telah tercapai 100%, sedangkan indicator yang ketiga mencapai 79,06% dari target 80%. Berdasarkan hal tersebut masih perlu dilakukan monitoring serta evaluasi pada rencana tindak lanjut yang masih dilaksanakan oleh peserta diklat sehingga semua indicator dapat tercapai. Kata kunci: petani, milenial, pelatihan, kapasitas ABSTRACT Millennial farmer capacity building training is carried out in the form of education and training which is summarized in capacity building training activities for millennial farmers. The objectives are to (1) prepare millennial farmers who are able to become agents of change who are empowered and able to empower the potential of existing resources in the community; (2) increasing the capacity of millennial farmers individually and in organizations to achieve goals and (3) creating a healthy, resilient and independent group of millennial farmers. CB training is carried out through technical guidance on 7 (seven) guidance activities through a participatory approach. The results of the activity show that the first and second indicators have been achieved 100%, while the third indicator has reached 79.06% of the 80% target. Based on this, it is still necessary to monitor and evaluate the follow-up plan that is still being implemented by the training participants so that all indicators can be achievedup plan that is still being carried out by the training participants so that all indicators can be achieved in accordance with the target, which means that the objectives of the activity are achieved. Keywords: farmer, millennial, training, capacity